Pelatihan Peningkatan Kompetensi Pedagogik Guru SMP ASA Cendekia - Ahmad Hatip; Windi Setiawan; Nuril Huda; Haerussaleh Haerussaleh; Boedi Martono (IKIP PGRI Bojonegoro, 2023)
Pedagogic competence is the ability possessed by the teacher in managing the learning process and interactions in teaching and learning activities with students. Now pedagogic competence has become part of the teacher competency test (UKG). UKG needs to be carried out with the aim of mapping the abilities of teachers in the fields of pedagogic competence and professional competence as well as a first step for selection to take part in teacher professional education (PPG). Teachers at ASA Cendekia Middle School often experience difficulties when dealing with pedagogic competency test questions, this has resulted in only a few teachers participating in PPG. Based on these problems, the community service team (abdimas) carried out three stages of community service. In the first stage, planning. At this stage, the solution offered is to discuss what materials are reinforced in pedagogic competency training for teachers. The second stage, implementation. At this stage, the University of Dr. Soetomo FKIP team conducted training to strengthen the pedagogic competence of Asa Cendekia Middle School teachers. The third stage, reflection. At this stage, the University of Dr. Soetomo FKIP team gave a pedagogic competency test, after which a discussion was held on each of the competency test questions. The result of this service is that the pedagogic competence of teachers is still low, so it needs to be improved by strengthening pedagogic competence in the next training.Kompetensi pedagogik adalah kemampuan yang dimiki oleh guru dalam mengelola proses pembelajaran maupun interaksi dalam kegiatan belajar mengajar bersama peserta didik. Kini kompetensi pedagogic telah menjadi bagian dari uji kompetensi guru (UKG). UKG perlu dilakukan dengan tujuan untuk memetakan kemampuan para guru dalam bidang kompetensi pedagogic dan kompetensi professional sekaligus sebagai langkah awal untuk seleksi mengikuti pendidikan profesi guru (PPG). Guru-guru di SMP ASA Cendekia kerap kali mengalami kesulitan ketika menghadapi soal-soal uji kompetensi pedagogic hal ini mengakibatkan hanya beberapa guru saja yang telah ikut PPG. Berdasarkan masalah tersebut, tim pengabdian masyarakat (abdimas), melaksanakan tiga tahapan pengabdian masyarakat. Pada tahap pertama, perencanaan. Pada tahap ini, solusi yang ditawarkan adalah berdiskusi mengenai materi apa saja yang dikuatkan dalam pelatihan kompetensi pedagogic bagi guru. Tahap kedua, pelaksanaan. Pada tahap ini, tim FKIP Universitas Dr. Soetomo melaksanakan pelatihan penguatan kompetensi pedagogic guru SMP Asa Cendekia. Tahap ketiga, refleksi. Pada tahap ini, tim FKIP Universitas Dr. Soetomo memberikan tes kompetensi pedagogik, setelah itu dilakukan pembahasan pada setiap soal tes kompetensi tersebut. Hasil dari pengabdian ini adalah kemampuan kompetensi pedagogic para guru masih rendah sehingga perlu ditingkatkan lagi dengan penguatan kompetensi pedagogik di pelatihan berikutnya